REMAJA PUTRI MEMPUNYAI PENGETAHUAN LEBIH BAIK TENTANG SEKS BEBAS - Ekawati (MEDIA ILMU KESEHATAN, 2012)
Background: Adolescence is a period of transition characterized by a change in the physic, emotion, and psychology. In adolescence there is an important development, namely cognitive, emotional, social and sexual development quickly. Sexual changes are conditions necessary to watch out for risk of adverse behavior that is sex-free. The risk of free-sex is less known by many adolescents. Lack of knowledge is caused by various factors such as customs, culture, religion and lack of information from the right source. Objective: This study investigated the differences in the level of knowledge about sex between adolescent boys and girls in class XI of SMA Muhammadiyah I of Magelang. Methods: This was a quantitative study with survey and analytic methods and a cross-sectional approach. Sample collection technique in this study was total sampling for male and female students of class XI of SMA Muhammadiyah I, Magelang. Data were taken by using questionnaires. Data analysis used univariable and bivariable analysis. Results: Most of the adolescent boys (77%) and girls (98.4%) had good knowledge about free-sex. Correlation of the level of knowledge about sex between adolescent boys and girls proved significant, with p = 0.03. Conclusion: Knowledge of adolescent girls about free-sex was better than that of adolescent boys. Adolescent boys are expected to put more effort in getting information about free-sex properly from a reliable source. Keywords: Knowledge, adolescent, free-sex